Intermediating Knowledge Exchange between Universities and Businesses - Yusuf, Shahid (2012)
The forging of links between universities and businesses is viewed increasingly as an important means of stimulating knowledge development that can lead to commercial innovation. Achieving effective knowledge exchange, however, requires the midwifery of different kinds of intermediaries often working in concert. Active and many faceted intermediation for the purposes of knowledge sharing and commercialization is essential when the knowledge is tacit or uncodified. The papers in this special section describe and discuss various intermediary mechanisms that assist universities in transferring knowledge and aiding the process of innovation. No single recipe is clearly superior but examining a variety of experiences helps to highlight the strengths of specific intermediary processes and to identify some of their shortcomings.